Preaching and harmony with other faiths |الدعوة والتآلف مع المعتقدات الأخرى - Ghilmanul Wasath (Al-Zahra : Journal for Islamic and Arabic Studies, 2010)
this article taks about the preaching methode and harmony live of muslim with other faiths as the neighboor or relationship.